Kualitas Oosit Kerbau dari Status Reproduksi Ovarium yang Berlainan - Hasbi Hasbi; Ni Wayan Kurniani Karja; Mohamad Agus Setiadi; Sri Gustina (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
In vitro embryo production relies on the quality of oocytes, however the quality is subjected to ovaries reproduction cycle. This study was conducted to observe the potency of buffalo ovaries from various reproductive cycle in producing quality oocytes. Collected pairs of ovaries from slaughter house were weighed and grouped of 5 according to the cycle. Oocytes were collected by slicing techniques, then selected based on quality. The results showed the average weight of buffalo ovaries of (+CL, +FD); (+CL, -FD); (-CL, +FD); (-CL, -FD) are 7.2 g; 5.5 g; 4.1 g; and 4.5 g respectively. No significant quality difference of produced oocytes between ovaries cycles (P>0.5). Good quality of collected oocytes were only 40-55%. Approximately 2-5 oocytes of grade A and 1-5 oocytes of grade B can be collected per pair of ovaries.